FAKTOR YANG MEMPENGARUHI KETEPATAN WAKTU PELAPORAN KEUANGAN PADA PERUSAHAAN YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2014 SAMPAI 2018 - Sri Anisa; Gusnardi Gusnardi; Mujiono Mujiono (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstrack: This study aims to analyze the factors that affect the timeliness of reporting financial statements on companies listed on the Indonesia Stock Exchange from 2014 to 2018. The population in this study is that there are 21 companies that do not report their financial reports on time for the 2014 to 2018 period. There are 9 companies selected as samples using purposive sampling. The data used in this study is secondary data, by collecting the required information from the internet in the form of financial reports 2014 to 2018. the techniques used to analyze the data are descriptive statistics, logistic regression, hypothesis testing. The results of this study indicate that profitability and liquidity have a significant effect on the timeliness of financial reporting, while company size and leverage have no significant effect on timeliness of financial reporting. Key Words: Timeliness, Profitability, Liquidity, Company Size, Leverage